The Glimpses of the 40th All India Rose Convention and Show — A short communication - TRIPATHY, LILYMOONY; PANDA, SUDARSHAN (Journal of Ornamental Horticulture, 2024)
Rose symbolizes romance, love, beauty, and courage. It has been regarded as the king or queen of flowers. Its multiple benefits and function has outcasted most of other flowers. The beauty of rose are comforting to people; the fragrance of rose calms stressed-out body and mind; the ingredients of rose can be a good source of nutrients and medicinal herbs; the hierarchical structures of rose petals have anti- reflection and light-harvesting abilities, which have the potential to be materials for various electronic product. Hada Bejar an actress by profession rightly said "Fragrance always stays in the hands that give the roses." Such convention has brought the common people and roses at a confluence so as to be a part in all fields of this world.